Mismatch Negativity and Impaired Social Functioning in Long-Term and in First Episode Schizophrenia Spectrum Psychosis - Murphy, Timothy K.; Haigh, Sarah M.; Coffman, Brian A.; Salisbury, Dean F. (Frontiers in Psychiatry, 2020)
Mismatch negativity (MMN) is sensitive to infrequent physical parameter changes in sounds. Both pitch-deviant MMN (pMMN) and duration-deviant MMN (dMMN) are severely reduced in long-term schizophrenia (Sz). Although symptom factors (positive, negative, cognitive) are inconsistently associated with MMN amplitude in Sz, several studies have shown smaller dMMN is associated with impaired social functioning in Sz. MMN is less reduced at the first psychotic episode in the schizophrenia spectrum (FESz). Meta-analyses indicate pMMN is not reduced, while dMMN shows moderate reduction. Associations between pMMN and dMMN and symptom clusters in FESz are also inconsistent, and associations with social functioning have not been reported. FESz and matched controls (n=40/group), and Sz and matched controls (n=50/group) were assessed for cognition, psychiatric symptoms, and social functioning, and underwent pMMN and dMMN testing. Sz showed reductions in pMMN (p =0.001) and dMMN (p =0.006) amplitude. By contrast, neither pMMN (p =0.27) nor dMMN (p =0.84) were reduced in FESz. However, FESz showed associations between pMMN and dMMN and negative symptoms and social functioning. More impaired MMNs in FESz were associated with increased negative symptoms and impaired social functioning, both current and in the year prior to the emergence of psychosis. These data suggest that the degree of pathological process occurring prior to the emergence of first psychosis as reflected by compromised social behavior prior to first break and reduced interpersonal communication and increased alogia at first break is indexed by pMMN and dMMN, putative biomarkers of disease progression sensitive to functional impairment.